A study of drug prescription patterns, disease-therapy awareness and of quality of life among patients with migraine visiting a tertiary care hospital in Mumbai, India - Bhide, Shruti; Verma, Pragya; Ravat, Sangeeta; Phirke, Chetan; Rao, Shirish (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Migraine is one of the leading causes of disability globally. There is scarcity of data on disease -therapy awareness and its correlation with demographic factors. Hence its was of interest to assess those along with quality of life in these patients. Methods: A Cross-sectional observational study was conducted in108 patients attending the Neurology and headache OPD at a tertiary care hospital between March 2017 and August 2018. Disease and therapy awareness among patients were evaluated using validated questionnaires and correlation was done with demographic factors. The severity of the disease and its impact on the patients’ quality of life were assessed using the migraine disability assessment scale. Results: The mean disease and therapy awareness scores were 9 and 7 respectively. Both had a positive correlation with education and socioeconomic factors. The quality of life was affected moderately in 48.1% of the patients followed by severely 32.4% of the patients. The average number of drugs prescribed per encounter was 3.05. NSAIDS were used more commonly as compared to Triptans for acute attacks. Conclusions: The disease and therapy awareness were fair and positively correlated with education/ socioeconomic status. However, a significant disability was found among patients even with treatment. This highlights the need for educating these patients for effectively controlling the disability.